Principal Management in Enhancing Educators' Work Motivation - Andri Halomoan; Samsidar Samsidar; Rahmah Yasrah Dalimunthe (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
Education and learning in schools will improve with effective management conducted by the school principal. The principal serves as the leader of the school and holds multiple roles, including management. Through effective management, the principal can interact, communicate, and carry out various activities with teachers to enhance the quality of the school and improve teachers' professional competencies. This study aims to examine the role of school management in increasing educators' work motivation at Ban Kadeng School, Narathiwat Province, Thailand. The research employs a descriptive qualitative method with a field approach, aiming to understand and describe social phenomena in-depth based on data obtained directly from the field. Data was collected through observation, interviews, and documentation. The data analysis techniques used include data reduction, data presentation, and data verification. The findings reveal that the school principal plays a crucial role in enhancing educators' work motivation through effective management at Ban Kadeng School. The principal acts as a goal-setter, overseeing planning, organizing, directing, and controlling policies, procedures, budgets, and school programs. This process actively involves teachers in both planning and implementation. In terms of execution, the principal conducts evaluations, and the results serve as the basis for future improvements and program development. Ban Kadeng's principal adopts a democratic leadership style, which effectively fosters a conducive work environment, supports teachers' professional development, and ensures that every decision is made through a consultative process involving all stakeholders. The principal also ensures a positive work environment and provides continuous support for teachers' professional growth.